New compositions of fluoroindate glasses with higher chemical resistance - Costa, B. J.; Soufiane, A.; Messaddeq, Younes [UNESP] (Sociedade Brasileira de Química, 1998)
In this paper, glasses in the systems In-Ba-Mg and In-Ba-Zn-Sr-Mg were water leachead at 80ºC showing surface degradation after 72 hours of leaching. The extent of such degradation is determined by the solubility and the concentration of the elemental fluorides that constitute the glasses. The formation of a layer of crystallized phases on the surface of the samples was observed. Small weight losses were registered and the absence of water on the glass matrix after the attack suggested that the use of MgF2 in the systems studied can lead to better results against moisture corrosion when compared to other fluoride glasses such as the fluorozirconates.
The chemical resistance of fluoride glasses in aqueous solution is a very important factor oncerning the technological applications of these materials
Keywords: glass; fluoroindate; water; resistance